Oceanic Drivers of Widespread Summer Droughts in the United States Over the Common Era - Seung H. Baek; Nathan J. Steiger; Jason E. Smerdon; Richard Seager (Geophysical Research Letters)
Abstract We examine oceanic drivers of widespread droughts over the contiguous United States (herein pan‐CONUS droughts) during the Common Era in what is one of the first analyses of the new Paleo Hydrodynamics Data Assimilation (PHYDA) product. The canonical understanding of oceanic influences on North American hydroclimate suggests that pan‐CONUS droughts are forced by a contemporaneous cold tropical Pacific Ocean and a warm tropical Atlantic Ocean. We test this hypothesis using the paleoclimate record. Composite analyses find a robust association between pan‐CONUS drought events and cold tropical Pacific conditions, but not with warm Atlantic conditions. Similarly, a self‐organizing map analysis shows that pan‐CONUS drought years are most commonly associated with a global sea surface temperature pattern displaying strong La Niña and cold Atlantic Multidecadal Oscillation (AMO) conditions. Our results confirm previous model‐based findings for the instrumental period and show that cold tropical Pacific Ocean conditions are the principal driver of pan‐CONUS droughts on annual timescales.